(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2026)
Microfinance institutions (MFIs) have become crucial instruments in the development of economic resilience in third world areas by availing financial services to the underserved population. This paper presents the purpose of MFIs in improving the economic resilience in Enugu State, Nigeria, in terms of their effects on income stability, entrepreneurship and poverty reduction. A mixed methods approach based on the results of primary data of 400 micro-entrepreneurs and secondary data of reports and studies identifies that MFIs play an important role in violence of household income and business development but obstacles such as high interest rates and accessibility still exist. The research fills knowledge gaps that exist in studies that are specific to a region since it aims to discuss the unique socio-economic environment of Enugu and provide solutions to enhance MFI effectiveness. Results highlight the necessity to design financial products personally, improve regulatory frameworks, and be digitally integrated to help become as resilient as possible. The paper provides practical recommendations to policy-makers and practitioners who want to make economic stability in Enugu State stronger.